Key Drivers of ASEAN Foreign Direct Investment - Zafar , Sehrish; Abdul Hadi, Abdul Razak (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the determinants of inward foreign direct investment (FDI) across four sectors (extractive, infrastructure, manufacturing and service sector) in selected six ASEAN countries (Malaysia, Indonesia, Singapore, Thailand, Vietnam and Philippine). Deploying seven institutional factors as the determinants of inward FDI (voice and accountability, political stability, government effectiveness, rule of law, regularity quality, control of corruption and technology activity index), this study adopts Static Panel Data approach as an estimation method that covers 16-year study period from 2001 through 2016. The empirical findings reveal that both country-specifics and sectorial-specifics influence the relative strength of these key FDI determinants and that every sector requires a discrete policy in attracting more FDI. Furthermore, the study reveals that one specific sector cannot be subsumed with other sectors nor can the distinctiveness of each sector be ignored. Any policy study that incorporates all sectors into a single inward FDI is likely to misguide practitioners as well as policy makers.